2004
DOI: 10.1016/j.jelechem.2003.09.025
|View full text |Cite
|
Sign up to set email alerts
|

A SERS investigation of the electrodeposition of Ag–Au alloys from free-cyanide solutions

Abstract: In this paper we investigated the electrodeposition of Ag-Au alloys from cyanide baths by in situ surface-enhanced Raman spectroscopy. The spectroelectrochemical investigation is complemented by electrochemical experiments (cyclic voltammetry and potentiostatic electrodeposition) and structural (X-ray diffraction), morphological (scanning electron microscopy) and compositional (energy dispersive spectroscopy) characterisation of the alloys. Electrochemical and spectroelectrochemical results on singlemetal elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 45 publications
4
34
0
Order By: Relevance
“…3 and indicates its evolution into large smooth globules and eventually to rough globules. Similar observations were found in the electrodeposition of Co powders [11] and Ag-Au alloys [12] where disperse growing entities eventually coarsened at their tips and evolved into compact entities. Formation of the spherical diffusion zones was mentioned to be the reason for the realization of compact growth at later stages.…”
Section: Resultssupporting
confidence: 80%
“…3 and indicates its evolution into large smooth globules and eventually to rough globules. Similar observations were found in the electrodeposition of Co powders [11] and Ag-Au alloys [12] where disperse growing entities eventually coarsened at their tips and evolved into compact entities. Formation of the spherical diffusion zones was mentioned to be the reason for the realization of compact growth at later stages.…”
Section: Resultssupporting
confidence: 80%
“…The size of the globules increased along the length of the dendrites. Similar observations were found in the electrodeposition of Co powders [4] and Ag-Au alloys [10] where disperse growing entities eventually coarsened at their tips and evolved into compact entities. Formation of the spherical diffusion zones was mentioned to be the reason for the realization of compact growth at later stages.…”
Section: Resultssupporting
confidence: 80%
“…For example, in the galvanostatic deposition of Au-Ag alloys, dendritic precursors were observed in the initial stages of deposition under mixed activation-diffusion controlled conditions. At higher potentials produced in the later stages of deposition, due to the onset of the spherical diffusion condition, poorly defined crystallites and globular morphologies were found [10]. In the case of the electrodeposition of Cu it has been shown that at relatively low current densities, deposits formed with protruded tips which eventually grew in the form of carrot-like structures under activation-controlled mechanisms [11].…”
Section: Open Accessmentioning
confidence: 99%
“…Au:Ag alloys in the form of a thin film, multilayer, a rod (e.g., wire), or in a suitable template can be made via electrodeposition [45][46][47][48][49]. In this case, Ag and Au cyanide salts [45][46][47] (or other salts in a thiosulfate solution [50]) are combined in a given ratio. Upon application of a sufficiently reductive potential to a working electrode immersed in this solution, the two salts can be electrodeposited together yielding the binary alloy.…”
Section: Alloy Preparationmentioning
confidence: 99%
“…Upon application of a sufficiently reductive potential to a working electrode immersed in this solution, the two salts can be electrodeposited together yielding the binary alloy. Au electrodeposition is kinetically favored, while Ag deposition is thermodynamically favored [45,47]. Films of varying Au:Ag atomic percent can be made by altering the deposition potential and/or solution composition [51].…”
Section: Alloy Preparationmentioning
confidence: 99%